Kompetensi Pedagogik Guru Matematika Berpengalaman: Motivasi, Kreativitas, dan Pendekatan Humanis di Era Digital - Syafni Defila Arinta; Rika Mutiara Shandi; Ryan Ramadhan; Muhammad Hafid Abdi; Ade Irma (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Pedagogical competence serves as an essential foundation for building an effective and meaningful learning experience for students. This study seeks to examine and describe how a high school mathematics teacher with 26 years of professional experience applies pedagogical competence in the classroom. A descriptive qualitative approach was adopted, with data gathered through in-depth interviews conducted with a single informant. The Miles and Huberman model was utilized for data analysis, covering data reduction, data display, and conclusion drawing, supported by theoretical triangulation to ensure data validity. Four primary indicators emerged from the findings: (1) planning structured learning activities through weekly or per-session schedules; (2) employing inspiring and innovative teaching methods using active learning strategies; (3) recognizing individual student characteristics through a personalized approach; and (4) integrating digital tools such as social media and YouTube as teaching inspiration. The study concludes that intrinsic motivation, a reflective mindset, and a humanistic approach are fundamental in sustaining pedagogical competence quality amid curriculum changes and evolving student behavior in the digital age.